Neuroimmunology of psoriasis: Possible roles for calcitonin gene-related peptide in its pathogenesis - Joshua Kotlyar; Richard D. Granstein (Brain, Behavior, & Immunity - Health)
The nervous system has a complex interplay with the immune system, especially at barrier sites such as the skin. This allows it to play a role in a variety of cutaneous inflammatory disorders such as psoriasis, exerting effects on various immune cells via effector molecules such as neuropeptides. In this review, we discuss the role of calcitonin gene-related peptide in modulating the immune system and inflammation, with a focus on psoriasis.